EXCELLENT MEDICAL-SURGICAL NURSING CARE MANAGEMENT FOR MRS. H WITH PULMONARY TB IN THE PULMONARY INPATIENT WARD, H. ADAM MALIK GENERAL HOSPITAL, MEDAN CITY - Samosir, Melin Samosir; Rosmani Sinaga; Adelina Sembiring; Era Handayani; Abdul Hafizh Alrasyid Siregar; Yoan Andini; Sriayu Manalu, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Pulmonary tuberculosis (TB) remains a major infectious disease and a serious public health problem in both Indonesia and globally. According to WHO data in 2024, Indonesia ranks second after India among countries with the highest tuberculosis burden. Globally, it is estimated that in 2023 there were 10.6 million new TB cases, with approximately 1.3 million deaths among HIV-negative individuals. Indonesia contributed around 10% of the global burden, with an estimated 1,060,000 cases and an incidence rate of 385 per 100,000 population. Pulmonary tuberculosis is an infectious disease that attacks the lungs, typically characterized by persistent cough, shortness of breath, and significant weight loss.This final report aims to describe the management of medical-surgical nursing care focused on "service excellent" principles for a patient with tuberculosis, identified as Mrs. H, who was hospitalized in the pulmonary ward of H. Adam Malik General Hospital, Medan, in 2025. The method used is a case study with a descriptive approach. Data were collected through interviews, direct observations, and review of medical records. The assessment revealed that Mrs. H complained of a persistent productive cough for two months, shortness of breath, decreased appetite, and severe weight loss from 45 kg to 33 kg. The established nursing diagnoses included ineffective airway clearance, impaired gas exchange, and nutritional deficits. Nursing interventions focused on airway management, oxygen therapy, and nutritional management. The implementation of care was carried out over three days, with ongoing evaluation using the SOAP method. The evaluations showed gradual improvements, although not yet fully resolved, thus requiring continued intervention by the ward nursing staff. The implementation of medical-surgical nursing care with a service excellent approach emphasizes patient-centered care, effective communication, comprehensive education, and multidisciplinary collaboration to achieve optimal outcomes. Nurses are expected to support patient recovery, prevent further complications, and improve quality of life through professional, empathetic, and humanistic services. This report is expected to contribute to the development of nursing science, particularly in infectious pulmonary disease management. Furthermore, it can serve as a reference for hospitals to improve the quality of nursing care according to standards and strengthen the role of nurses as the frontline in tuberculosis prevention and management.